A New Proposal Using a Turbine in the Reactor with a Cavitation System in the Biodiesel Synthesis - Ferreira, Sérgio L. [UNESP]; Módolo, Délson L. [UNESP]; Scalon, Vicente L. [UNESP]; Sanchez, Luiz E. A. [UNESP]; Avallone, Elson; Polito, Wagner L. (Springer Nature, 2017)
The present research investigates the effect of a cavitation system with a turbine in comparison to the vigorous stirring on the process of biodiesel synthesis by the transesterification reaction using oil (triglycerides) and anhydrous ethanol. The proposed cavitation equipment consists of a device that works as a turbine (novelty) and not by a pump. The turbine coupled to cavitation system showed a substantial degree of intensification in comparison to the conventional approach reported in the literature. An ester content of 96.4 % in a 5 min reaction was obtained using conventional approach with vigorous stirring of 9500 rpm and ethanol/oil molar ratio of 8:1 and 1.0 wt% catalyst concentration. An ester content of 98.5 % was obtained using ethanol/oil molar ratio of 6:1, 1.0 wt% catalyst concentration and 60 s reaction by cavitation system with a turbine. The properties analyzed of biodiesel, such as density, viscosity, cetane number, cloud point, cold filter plugging point and flash point are within the limit values established by standard methods.
Keywords: Biodiesel; Cavitation system; Electric consumption; Ester content; Turbine; Vegetable oil